A compact SiC photovoltaic inverter with maximum power point tracking function. (1st January 2017) - Ando, Yuji; Oku, Takeo; Yasuda, Masashi; Shirahata, Yasuhiro; Ushijima, Kazufumi; Murozono, Mikio
Highlights: A maximum power point tracking controller was integrated into a SiC inverter module. Size of the inverter is just one third of commercial Si inverters available today. The conversion efficiency was 3% higher than that of the commercial Si inverters. Abstract: A compact 150 W photovoltaic inverter was developed using SiC devices, which integrated a maximum power point tracking charge controller and a direct current (DC) - alternating current (AC) converter into a single module. The DC-AC converter circuit was built with four SiC metal-oxidesemiconductor field-effect transistors, while the DC-DC converter circuit built with four SiC Schottky barrier diodes. An increase of the switching frequency led to the module of a reduced size (250 × 180 × 28 mm 3 ), which is just one third volume of a commercial Si-based inverter available today. Besides being compact, the conversion efficiency of the DC-AC converter was approximately 3% higher than that of the commercial Si-based inverter. In addition, the MPPT controller showed a conversion efficiency exceeding 96%, which raised the total efficiency under practical operation conditions up to 86%.